The axiological orientation of students’ personalities - Sergey I. Kudinov (Psychology in Russia: State of Art, 2018)
Background. Our empirical research and analysis revealed characteristics of the axiological orientation of students’ personalities. Objective.We identified the principal types of orientation, dominant values, and attitudes of the personality in the motivational-needs sphere through a variety of validated and reliable techniques and methods. Design We understand the axiological orientation of the personality as a relatively stable set of values, motivations, needs, and moral structures produced through the lens of actions, in and through various spheres of social life, which describes complex system of a person’s perception of him-/herself, his or her perceptions of others, and his or her attitude towards work and other activities. Results. The results of the empirical research demonstrate that a set of axiological, motivational, and need characteristics form pragmatic-professional, social-communicative, or individual-egoistic types of axiological orientation of the personality, which in turn describe the subject’s attitude to the surrounding external reality and to him/herself. The pragmatic-professional type of person is dominated by values such as work, results, money, and process. The least attractive value to this type appears to be power. Respondents with a social-communicative type of axiological orientation have altruism, result and money as their main personal values. Values such as egocentrism, power, money, and freedom are a distinguishing mark of those with the individual-egoistic axiological orientation. Conclusion. This study also addresses how and through what patterns and mechanisms the axiological orientation of students’ personalities is expressed, which could enable professionals to develop educational programs aimed at harmonizing and aligning societal values and the individual’s attitudes.